PENGARUH KARAKTERISTIK PERUSAHAAN TERHA- DAP PENGHINDARAN PAJAK PADA PERUSAHAAN SEK- TOR PERTANIAN SUB SEKTOR PERKEBUNAN BEI PADA TAHUN 2018-2020 - Irwan Syahputra Tamba; Paul Eduard Sudjiman (Jurnal Ekonomis, 2022)
This research aims to analyze the effect of company characteristic on tax avoidance on BEI plantation sub sector companies in 2018-2020. The population of this research was 19 companies listed on the Indonesia Stock Exchange during 2018-2020 observation period. The sampling method used was purposive sampling, so that 13 sample companies were obtained for 3 years of observation (2018-2020) with 39 data of analysis. The research data was obtained from annual reports from sample companies which were downloaded from the BEI website. The result of this research indicate that return on assets (ROA) has a significant effect on tax avoidance and company size has an effect on tax avoidance.